Hubungan Antara Durasi Penggunaan Gadget Pada Anak Dengan Sosial Emosional Anak Usia Dini (4-5 Tahun): The Relationship Between Gadget Usage Duration in Children and the Socio-Emotional Development of Early Childhood Children (Ages 4-5) - Ardyansah, Rizki Bahtiyar (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Background Over time, one thing that is inevitable is the rapid advancement of science and technology, making it accessible to people of all ages around the world. Besides the impact of technological advancements on its users, the use of technology has provided significant benefits to various age groups, especially adults, and even children. This technology includes computers, mobile phones, laptops, and many other types of devices. Gadgets are the most well-known technology among the general public; a gadget is a set of electronic devices used for communication, documentation, social networking, and entertainment. Based on the issues above, the question posed in this study is, "Is there a relationship between gadget use in children and the social-emotional development of early childhood (ages 3-5)?" This study uses a quantitative research method with a Probability Sampling technique. The population in this study consists of children aged 4-5 years at TK Dharma Wanita 1, TK Dharma Wanita 2, and TK Dharma Wanita 3, totaling 127 children. The research results obtained a significance value of p = 0.000 < 0.05. Therefore, this indicates that there is an effect of the duration of gadget use on the social-emotional development of early childhood children. The r value = -0.663 indicates that the two variables have a strong negative relationship between the duration of gadget use and the social-emotional development of early childhood children, where long gadget use leads to low social-emotional development in young children. Based on the research results, the relationship between the duration of gadget use and the social-emotional development of early childhood children can be concluded as follows: The research results show that most respondents use gadgets for more than 1 hour a day. The research results also show that most respondents have low social-emotional development.